Synthesis of Pectin-poly(acrylonitrile) Superabsorbent Hydrogel with Salt and pH Responsiveness Properties - Sadeghi, Mohammad; Nasrolahi, Morteza; Yarahmadi, Mojgan (Asian Journal of Chemistry, 2011)
In the present paper, attention is paid to synthesis and investigates swelling behaviour of a superabsorbent hydrogel based on pectin (Pec) and polyacrylonitrile. The physical mixture of pectin and polyacrylonitrile was hydrolyzed by NaOH solution to yield pectin-poly(sodium acrylate-co-acrylamide) superabsorbent hydrogel. The nitrile groups of polyacrylonitrile were completely converted to a mixture of hydrophilic carboxamide and carboxylate groups during alkaline hydrolysis followed by in situ crosslinking of the polyacrylonitrile chains by the alkoxide ions of pectin. A proposed mechanism for hydrogel formation was suggested and the structure of the product was established using FTIR and SEM spectroscopies. Under the optimized conditions, maximum capacity of swelling in distilled water was found to be 523 g/g. The absorbency of the synthesized hydrogels was also measured in various salt solutions. Results indicated that the swelling ratios decreased with an increase in the ionic strength of the salt solutions. In addition, swelling capacity was conducted in solutions with pH ranged from 1 to 13. The pectin-poly(sodium acrylate-co-acrylamide) hydrogel exhibited a pHresponsiveness character so that a swelling-deswelling pulsatile behaviour was recorded at pHs 2 and 8.